Global compensation and benefits : developing policies for local nationals - Herod, Roger, 1944- (Global HR management series., 2008)
A presentation of the critical issues in developing effective benefits and compensation policies for individuals working abroad under local terms and conditions, this guidebook addresses such topics as pay practices, short- and long-term incentive plans, health care, and retirement benefits. Armed with the attest research and data on this emerging corporate issue, this indispensible resource also features a full summary of the current trends in benefits programs.